Ideal Regulation on Endorser Responsibility for Consumer Losses from Promotional Actions by Endorsers - Mufidah, Lailatul; Kusumadara, Afifah; Eta Widyanti, Yenny (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
Advertising strategies through social media are increasingly being chosen by business actors to market their goods and/or services. The existence of advertising strategies through social media has given birth to a new term known as endorsers. The rapid development in the world of advertising is not balanced by the development of laws in the legislation in Indonesia which is specifically regulated through Law Number 8 of 1999 concerning Consumer Protection. The purpose of this study is to find out the ideal regulation of endorser liability for consumer losses due to promotional actions carried out by endorsers. The research method used in this study is normative legal research with a conceptual approach, a statutory approach, and a comparative approach with the Code of Federal Regulations (CFR) Part 255 on Guides Concerning the Use of Endorsements and Testimonials in Advertising. The results of this study are the urgency for legislation in Indonesia to regulate endorsers in detail and explicitly so that endorsers can be held accountable for promotional actions carried out by them.